2019
DOI: 10.3390/agronomy9110730
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Seasonal Changes in Soilless Greenhouse Sweet Peppers

Abstract: This study was commissioned to study the effect of the growing season on the antioxidant components of greenhouse sweet pepper crops, which is of scientific interest because of their possible beneficial health effects. The total antioxidant activity (estimated by ferric reducing antioxidant power-FRAP assay) major antioxidants (ascorbic acid, phenolics and carotenoids) and taste fruit quality characteristics (soluble solids, titratable acidity, dry matter and sugars) were recorded in soilless-grown sweet peppe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…For salt stress, several studies in the model-crop tomato reveal positive impacts of mild stress on fruit quality (e.g., antioxidant capacity and nutritional value) [47,48]. Low UV radiation reduces the antioxidative capacity and, therefore, the fruit quality of bell pepper fruits [49]. Additional UV radiation may help to overcome this problem and, at the same time, induce the production of valuable SM in the leaves.…”
Section: Implications and Future Challengesmentioning
confidence: 99%
“…For salt stress, several studies in the model-crop tomato reveal positive impacts of mild stress on fruit quality (e.g., antioxidant capacity and nutritional value) [47,48]. Low UV radiation reduces the antioxidative capacity and, therefore, the fruit quality of bell pepper fruits [49]. Additional UV radiation may help to overcome this problem and, at the same time, induce the production of valuable SM in the leaves.…”
Section: Implications and Future Challengesmentioning
confidence: 99%
“…Several authors reported neutral or positive responses of product quality to mild stress [42]. Low UV radiation reduces the antioxidative capacity and therefore the fruit quality of bell pepper fruits [43]. Additional UV radiation may help to overcome this problem and at the same time induce the production of valuable SM in the leaves.…”
Section: Implications and Future Challengesmentioning
confidence: 99%
“…Carotenoids form part of the antioxidant system of plants and play a vital role in protecting the plant against oxidative stress [ 36 ]. Therefore, there is a close relationship between carotenoid content and antioxidant activity [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Carotenoids form part of the antioxidant system of plants and play a vital role in protecting the plant against oxidative stress [ 36 ]. Therefore, there is a close relationship between carotenoid content and antioxidant activity [ 36 ]. There was no significant difference between conventionally and bokashi grown fruit at harvest and after storage ( Table 6 ).…”
Section: Resultsmentioning
confidence: 99%